Effects of "Jin Batu" (Strobllanthes Crispus) Extract on Serum Lipid Profile and Antioxidant Status of Hypercholesterolemia-Induced Rabbits - Ismail, Nurhafzan Anis (2004)
Hypocholesterolemic, anti-atherogenic, toxicity effects and changes in the antioxidant status of Strobilanthes crispus extract (SCE) in atherogenically induced animal model were studied. As much as, 58.05 ± 1.08% total dietary fiber (TDF), 54.61 ± 3.92% insoluble dietary fiber (IDF) and 6.01 ± 0.82% soluble dietary fibers (SDF) was found in the Strobilanthes crispus (SC) ground, dried leaves (AOAC method). At concentration of 0.32-5.12 mg/ml, SCE showed 3.76 ± 7.45% to 56.72 ± 2.49% scavenging effect on 1,I-diphenyl-2-picrylhydrazyl (DPPH) radicals with ECso of 2.21 mg/ml. The total flavonoids content in SC fresh leaves and ground, dried leaves were 0.99 ± 0.04 % and 0.46 ± 0.06 %, respectively. Quercetin was found highest in SC ground, dried leaves, followed by kaempferol, luteolin and rutin while kaempferol was found highest in SCE, followed by quercetin, luteolin and rutin (HPLC method). Twenty-four adult female New Zealand white rabbits (1.8-2.5 kg) were randomly assigned into four groU!1S (n=6/group) and fed with normal diet; negative control (NC),0.25% high cholesterol diet (HCD); positive control (PC), 0.25% HCD + SCE (0.2% of diet); SC and 0.25% HCD + simvastatin (SV) (20 mg/kg body weight); SV for 12 weeks. Food and water were given ad libitum. Blood samples were biweekly drawn for serum lipid profiles, alanine amino transferase (ALT), gamma glutamic transpeptidase (GGT), urea, creatinine, conjugated diene (CD), malondialdehyde (MDA) levels of serum, liver, kidney, heart and brains. After being killed, ascending aorta, liver, kidney and heart tissue specimens were excised immediately and prepared for the histopathological studies. PC group showed significantly increased (p<0.05) TC, LDL and HDL levels, HDL/TC ratio, LDL/HDL ratio, atherogenic index, CD levels, serum, heart, liver and kidney MDA levels, and relative liver weight. Significantly (p<0.05) elevated HDL and reduced kidney MDA levels were observed in SC group, while significantly reduced (p<0.05) TC, LDL, heart, liver and serum MDA levels found in SV group. Massive macrophages, foam cells and atheroma plaque formation were detected, which slightly increased intima to media ratio and thickened the PC group's aorta. Moderate to fairly intense lymphocyte infiltration, slight macrovesicular lipid droplets, edematous hepatocytes, inconsistent binucleated cells and vacuolated cytoplasm were found in PC group's liver. Significantly prevented (p<0.05) atheroma plaque formation, both treatment groups showed lesser aortas' thickening, irregular mild edematous hepatocytes, binucleated cells, vacuolated cytoplasm and lipid droplets inhibition. Though mild lymphocyte infiltration was found in SV, such changes were almost invisible in SC group. Briefly, SC plant may possess the hypocholesterolemic, anti-atherogenic and hepatoprotective effect due to the antioxidative properties of flavonoids, i.e. quercetin, kaempferol, luteolin, rutin and catechin.